La atribución de los jueces de trabajo para el trámite del visto bueno contemplado en el código del trabajo - Cueva Cango, Verónica Marlene (2014)
The Article 621 of the Labour Code, authorizes the Labour Inspector of the approval process for any of the grounds referred to in Article 173 and 173 of the same Code. The same Article 589 of the Labor Code states that when the inspector any previously known case according to Article 621 of this Code, it shall report its decision to grant the approval. So the rules firmness and authority to remove one of the main responsibilities of the Inspectors, such as grants or deny Endorsement, which can be challenged in court. But there is also a clear example of self-estimation of the authority of the Inspector, for according to Article 191 of the Labour Code provides that if the employee requests and the approval obtained for any of the grounds of Article 173 of the Code, shall be entitled to compensation for unfair dismissal; however, what happens in practice is that the worker accomplishes nothing despite his success in action Views Well, inspectors are hesitant to provide for the payment of compensation under the provisions of this standard is met and all forms of matter is discussed at trial. For these circumstances it makes sense to give him authority to process applications for approval, and finally cases these resolutions be aired in court before the judge of the work, the attribution of these considerations should be given to the judges.